2014
DOI: 10.15274/nrj-2014-10098
|View full text |Cite
|
Sign up to set email alerts
|

Potential of F-18 PET/CT in the Detection of Leptomeningeal Metastasis

Abstract: SUMMARY -Leptomeningeal metastasis (LM) is a rare but increasingly common condition in which malignant cells migrate to the meninges. The gold standard for diagnosing LM is detection of cancer cells in the cerebrospinal fluid (CSF). Contrast enhanced-magnetic resonance imaging (CE-MRI) is also used to diagnose LM. We describe a case of LM in which CE-MRI of the neuroaxis was initially negative for meningeal enhancement but F-18 fluorodeoxyglucose positron-emission tomography/computed tomography (F-18 FDG PET/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Manifestations of MC in PET-CT: the abnormal appearance of MC in PET-CT may be seen earlier than enhanced MR. For the patients with negative partial enhanced MR, the abnormity can be found in PET-CT. However, we have not seen much related reports so far, and according to the cost of PET-CT, it cannot be widely used and carried out in Chinese clinical practice [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Manifestations of MC in PET-CT: the abnormal appearance of MC in PET-CT may be seen earlier than enhanced MR. For the patients with negative partial enhanced MR, the abnormity can be found in PET-CT. However, we have not seen much related reports so far, and according to the cost of PET-CT, it cannot be widely used and carried out in Chinese clinical practice [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although up until now 18 F-FDG PET has been employed in few cases, different authors suggested its use as a supportive technique in intracranial LC diagnosis [ 23 ], either using 18 F-FDG [ 14 , 16 , 17 ] or 11 C-methionine [ 15 ] as radiotracers, especially when MRI and CSF data were initially inconclusive [ 14 , 16 , 17 ]; the evidence of an intense tracer uptake could be highly suspicious for LC, even if not specific, being present also in inflammatory disorders (infectious meningitis, neurosarcoidosis, etc.). Moreover, PET/CT could also be a valid alternative diagnostic tool as imaging procedure when contrast MRI cannot be performed for technical reasons, for instance in a patient with a pacemaker, as reported in the present study, but also in patients in whom the precarious health conditions may prevent lumbar punctures for CSF evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among the diagnostic imaging procedures, brain 18 F-fluorodeoxyglucose ( 18 F-FDG) and 11 C-methionine positron emission tomography (PET) and PET/computed tomography (CT) [ 14 , 15 ], have also been employed in LC diagnosis; however, up to date, only few cases of spinal and intracranial LC have been reported, more frequently derived from breast and lung cancers, all with positive results suspected for LC, and confirmed by repeated CSF cytology exams positive for tumor cells [ 14 , 15 ]. Furthermore, in some cases reported in different studies with negative CSF for tumor cells, the presence of distant bone metastases at whole-body (WB) CT and 18 F-FDG PET, which is known to have remarkably improved the management of cancer patients, was sufficient to clarify leptomeningeal lesion as LC [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent case reports have documented both intracranial and extracranial LC on 18 F-FDG PET/CT. [ 8 9 10 11 ] FDG PET/CT can occasionally pick up LC if careful attention is paid to patterns of LM spread. Multiple factors may explain the observed low sensitivity of 18 F-FDG PET/CT for detecting LC.…”
Section: Discussionmentioning
confidence: 99%